2022
DOI: 10.1002/jbt.23285
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses as early and reliable biomarkers of organophosphate and carbamate pesticides intoxication: A systematic literature review

Abstract: Inhibition of cholinesterase (ChE) activity has been long considered as the main diagnostic method of organophosphate (OP) and carbamate pesticides poisoning; however, it has been shown that ChE activity may also be altered due to exposure to other non-organophosphorus toxicants and variety of different medical conditions. Hence, to avoid misdiagnosis, we aimed to systematically review available documents to look for additional biomarkers of OP and carbamate poisoning. The electronic databases in addition to G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 93 publications
0
4
0
1
Order By: Relevance
“…Carbamates usually have a shorter environmental persistence compared to organophosphates. Examples include carbaryl, methomyl and propoxur [ 33 , 34 ]. Both insecticides kill target bugs by interrupting nerve signal transmission [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carbamates usually have a shorter environmental persistence compared to organophosphates. Examples include carbaryl, methomyl and propoxur [ 33 , 34 ]. Both insecticides kill target bugs by interrupting nerve signal transmission [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review identified additional biomarkers such as β-glucuronidase, neuropathy target esterase, amylase, and lipase that could improve the diagnosis of organophosphate and carbamate poisoning. These biomarkers can aid in better management and early identification of patients at risk of severe outcomes, thereby enhancing treatment effectiveness [10].…”
Section: Resultmentioning
confidence: 99%
“…Nanotoxicology is a part of nanosciences that considers the side effects of nanomaterials [46][47][48][49]. With increasing biological applications, concerns about the safety and toxicity of materials on the cells of living organisms, especially humans, have increased [50][51][52][53][54][55][56]. The size, surface charge, and concentration of nanomaterials are some of the factors that can affect the toxicity of nanoparticles.…”
Section: Cell Toxicity Properties Of Biosynthesized Nanocompositesmentioning
confidence: 99%